TINGKAT KEPUASAN KONSUMEN KUE TRADISIONAL “KIOS DANNY ANGGUR” DI PUSAT KULINER AIRMADIDI KABUPATEN MINAHASA UTARA - Alouw, Cindy Pricilia; Kumaat, Ribka M.; Olfie, Benu L. S. (Sam Ratulangi University, 2022)
The objective of this research is to determine the level of customer satisfaction of the Traditional Cake “Danny Anggur Stall” at the Airmadidi culinary center, North Minahasa Regency seen from the product, price, place, and service variables. This research was conducted from September to October 2021, using primary data and secondary data using accidental sampling technique as a sampling method and 30 respondents. The data analysis method used is descriptive data analysis using a Likert Scale. The results showed that the level of consumer satisfaction of traditional cake